2017
DOI: 10.1155/2017/8572509
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteome Alterations in Patients with Cognitive Impairment after Traumatic Brain Injury Revealed by iTRAQ-Based Quantitative Proteomics

Abstract: Background. Cognitive impairment is the leading cause of traumatic brain injury- (TBI-) related disability; however, the underlying pathogenesis of this dysfunction is not completely understood. Methods. Using an isobaric tagging for relative and absolute quantitation- (iTRAQ-) based quantitative proteomic approach, serum samples from healthy control subjects, TBI patients with cognitive impairment, and TBI patients without cognitive impairment were analysed to identify differentially expressed proteins (DEPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…MV/e are membrane-bound nanovesicles that serve as important mediators of intercellular communication by transporting molecular signals, including proteins, mrna and micrornas, between cells (20,21). High-throughput proteomics technology has been used to identify underlying mechanisms associated with the initiation and development of numerous types of cerebral disease (22)(23)(24). However, to the best of our knowledge, few studies have investigated the molecular mechanism of bilirubin-induced neurotoxicity based on proteomics techniques or extracellular MV/e (12,25,26).…”
Section: Quantitative Proteomic Characterization Of Microvesicles/exomentioning
confidence: 99%
“…MV/e are membrane-bound nanovesicles that serve as important mediators of intercellular communication by transporting molecular signals, including proteins, mrna and micrornas, between cells (20,21). High-throughput proteomics technology has been used to identify underlying mechanisms associated with the initiation and development of numerous types of cerebral disease (22)(23)(24). However, to the best of our knowledge, few studies have investigated the molecular mechanism of bilirubin-induced neurotoxicity based on proteomics techniques or extracellular MV/e (12,25,26).…”
Section: Quantitative Proteomic Characterization Of Microvesicles/exomentioning
confidence: 99%
“…Xiong et al also identified that this protein was differentially abundant, but its role in this mood disorder was not elucidated. 58 Regarding beta-2-glycoprotein 1 (or ApoH), the levels of this protein are admittedly elevated in SCZ patients. 59 For instance, ApoH has been suggested as a specific biomarker for SCZ or other psychotic disorders, or predisposition thereto.…”
Section: Metallobiomolecules Evaluationmentioning
confidence: 99%
“…The aim of this study was to identify differential expressed proteins (DEPs) with proteomic approach between PND and non-PND patients who underwent transurethral resection of the prostate (TURP) under combined spinal and epidural analgesia to identify potential predictors of PND, which was done through isobaric tags for relative and absolute quantitative (iTRAQ) technology. iTRAQ was a quantitative proteomic approach developed on recent years [21] and a powerful tool in not only characterizing protein expression profile but also biomarker identification. Thus far few researches regarding the proteomic profile of PND have been reported.…”
Section: Introductionmentioning
confidence: 99%